PERAN ASEAN SENIOR OFFICIALS ON DRUG MATTERS (ASOD) DALAM MENANGGULANGI PERDAGANGAN OPIUM 2006-2013 - Siegers, Zefanya Yolanda; Utomo, Tri Cahyo; Paramasatya, Satwika (Journal of International Relations, 2016)
The Golden Triangle is a border area of three Southeast Asia countries; i.eLaos, Myanmar, and Thailand. The Golden Triangle is the largest opiumproducer in the region. It causes Southeast Asia become vulnerable of drugstrafficking. Southeast Asian countries are aware of the danger of drugstrafficking, which later brought out the issue to ASEAN. In dealing with thisproblem, ASEAN established ASEAN Senior Official on Drugs Matters (ASOD),a special committee board in drugs trafficking. This research aimed todescribe ASOD roles in coping drugs trafficking in Golden Triangle from 2006to 2013. This research employed neoliberal institutionalist theory emphasizingon the concept of cooperation among states. The method is qualitative usingdescriptive analysis through library research. The results of this researchindicate that ASOD playes role as a facilitator of interstate cooperation interms of drugs trafficking among ASEAN members. This role is compatiblewith the basic assumption of neoliberal institutionalist theory arguing thatinstitution can bridge the gap between states preferences on particular issues.Yet, this research found that the role of ASOD in combating drugs trafficking isnot succeed due to its interent lack of legitimacy to make legal bindingdecisions.